Penerapan Sistem Kesehatan Dan Keselamatan Kerja Menggunakan Metode Strenght Dan Weakness Di PT Energi Cahaya Industritama Samarinda Provinsi Kalimantan Timur - Siti Fadlah Musarofah; Agus Winarno; Henny Magdalena; Windhu Nugroho; Lucia Litha Respati (MINERAL, 2022)
Research on the application of the OHS system is carried out with the aim of analyzing things in the application of K3. The research method uses a descriptive method in the form of a questionnaire. The results of the research questionnaire the highest percentage included in the strength (strenght) including the use of PPE 83.9% agreed that it was applied followed in an orderly manner, promotions and strategies and the application of K3 64.5% strongly agreed, the existence of PPE training that was applied 74.2% agree. The results of the weakness analysis (Weakness) that the highest percentage of the results of the questionnaire diagram are incomplete first aid facilities 80% agree, the workplace is not conducive, planning for implementing K3 strategies, providing emergency facilities for accidents 83.9%, periodic initial checks to employees 74.2% quite agree.